The effect of cultural values and perceived inclusive leadership on employee organisational citizenship behaviour and intention to leave : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (Psychology) at Massey University, New Zealand - Joseph, Siqi (Skee) (Massey University, 2024)
Workplace inclusion had increasingly gained attention in the rapid expansion of globalization and multi-cultural workforces (e.g., Chen & Tang, 2018; Rankin-Gomez, 2011). Behind any organisational culture and practices, leaders were thought to be the driver of building a diverse workforce, displaying inclusive behaviours, implementing inclusive practices and offering equitable treatment to all individuals (Shore et al., 2011; Myers, 2023). Inclusive leadership and its facilitating effect on individual, team and organisational outcomes has attracted increasing attention in the last decade around the world, however no studies have explored the influence of inclusive leadership in New Zealand. By collecting data from professionals (n=99) across industries in New Zealand, this study examined the effect of perceived inclusive leadership (PIL) on different forms of organisational citizenship behaviours (OCB), as well as its impact on employee’s intention to leave (ITL). Exploring the role of cultural values as a mechanism through which perceived inclusive leadership assert influence was another focal point of this study. This study revealed the positive effect of PIL on organisation citizenship behaviours directed at the organisation (OCBO) and its negative effect on intention to leave. Surprisingly, no relationship was found between PIL and organisational behaviours directed at individuals (OCBI). Individualism showed a positive association with OCBO and ITL, whereas collectivism was positively related to OCBI. Despite of these associations, there was no evidence supporting the moderating effect of cultural values individualism on the relationship between PIL and OCBO or ITL, nor the moderating effect of collectivism on the relationship between PIL and OCBI. This study contributes to the existing literature by highlighting the complex dynamics between leadership, cultural values, and employee behaviours in New Zealand, providing valuable insights for leaders and HR professionals aiming to foster inclusive and supportive work environments.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)